2018
DOI: 10.1039/c7sc03712k
|View full text |Cite
|
Sign up to set email alerts
|

A three-in-one-bullet for oesophageal cancer: replication fork collapse, spindle attachment failure and enhanced radiosensitivity generated by a ruthenium(ii) metallo-intercalator

Abstract: [Ru(phen)2(tpphz)]2+ simultaneously inhibits DNA replication, blocks mitosis and enhances DNA-damaging ionising radiation in oesophageal cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 65 publications
1
45
0
Order By: Relevance
“…In the first proteomic study involving kinetically inert ruthenium complexes, we found that these mononuclear complexes induce protein expression changes that are indicative of both DNA damage and oxidative stress responses. This first observation is consistent with previous studies confirming that binding directly stalls DNA replication forks, 51 however the up-regulation of proteins associated with oxidative stress suggest the complexes have a second mode of action. Although the complexes described by MacDonnell and coworkers are also cytotoxic through oxidative stress they contain ligands that Ð unlike tpphz 131 Ð are themselves redox active in biological conditions.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the first proteomic study involving kinetically inert ruthenium complexes, we found that these mononuclear complexes induce protein expression changes that are indicative of both DNA damage and oxidative stress responses. This first observation is consistent with previous studies confirming that binding directly stalls DNA replication forks, 51 however the up-regulation of proteins associated with oxidative stress suggest the complexes have a second mode of action. Although the complexes described by MacDonnell and coworkers are also cytotoxic through oxidative stress they contain ligands that Ð unlike tpphz 131 Ð are themselves redox active in biological conditions.…”
Section: Discussionsupporting
confidence: 92%
“…Complexes investigated in this study Like the dinuclear system, the mononuclear intercalating complex [Ru(phen)2(tpphz)] 2+ , , is taken up by cells, and shows cellular DNA binding; 50 however, it also displays cytotoxicity comparable to cisplatin and its potency is retained even in cisplatinresistant cell lines. 50 Unsurprisingly given its mode of interaction with DNA, , interferes with DNA replication 51 and it is a potent radiosensitizer. 51 Yet, a more detailed understanding of the cellular responses it induces, including cell death mechanisms, is still to be developed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phototoxicity of Ru complexes arises from two different mechanisms. One mechanism is singlet oxygen ( 1 O 2 ) sensitization using Ru complexes for photodynamic therapy (PDT) . The other mechanism is uncaging cytotoxic ligands or Ru species via ligand photosubstitution reactions for photoactivated chemotherapy (PACT) …”
Section: Introductionmentioning
confidence: 99%
“…[13,16,17] The extension of the dppz ligand with additional rings for example, leads to powerfula nti-tumour properties. [18][19][20] Gaining insight into the manner in which these complexes bind to their target is therefore of importance,w here a deeper structuralk nowledge allows for the superior design of more specific DNA binders. In one recent report, for example, ar apid screening approach was used to identify structural selectivity usingr acemic mixtures of ar ange of halide derivatives of [Ru(bpy) 2 dppz] 2 + ,a nd including the 11-Br analogue of the complex, studied in this work.…”
Section: Introductionmentioning
confidence: 99%